Triple helix and its implications in the Brazilian context - Marcos Aurélio Brambilla; Maria Ligia Ganacim Granado Rodrigues Elias; Viviane Sartori (Innovation & Management Review, 2025)
This study aims to analyze the triple helix model and its implications in the Brazilian context.A content analysis was conducted using the methodology developed by Bardin (2011), with support from the Iramuteq software, to examine the theoretical foundations of articles related to the topic.The research identified several obstacles hindering the efficiency of Brazil's innovation process. These include insufficient integration among stakeholders within the helix, the need to adapt the triple helix model to regional specificities and challenges in effectively incorporating civil society and environmental concerns into the framework.Including civil society and environmental dimensions as additional elements in the helix structure presents an opportunity to enhance the innovation process. This highlights the need for cultural shifts to enable effective collaboration among the helices.The findings contribute to the formulation of policies, strategies and initiatives aimed at promoting sustainable development and innovation in Brazil.
Keywords: 650; Innovation; Triple helix; Sustainable development; Civil society; Environment; Content analysis